The birth of experience - Eigen, Michael (Karnac Books, 2014)
The birth of experience goes on all life long. Giving birth to oneself involves many processes. The first chapter of this book expands on Eigen's final talk on "Psychoanalysis and Kabbalah" for the New York University Postdoctoral Contemplative Studies Project, and focuses in particular on an intertwining of beauty and destruction. Beauty is the heart of the Kabbalistic Tree of Life, intricately linked both to other capacities and to catastrophic devastation. Interestingly, Bion also links faith and catastrophe, and writes of psychoanalytic "beauty", thereby creating a rich dance of psychoanalysis with Kabbalah. Winnicott adds his own special touch, associating the fate of a vital spark with trauma as the personality begins to form, and with the work of spontaneous recovery that is a profound part both of living and of therapy sessions. The second part of the book is new and focuses on birth processes at different ages and situations, exploring in detail how psychoanalysis interweaves with themes from life, clinical work, and Kabbalah. Failed birth processes are part of living but so is the need to "midwife" existence. Eigen suggests that there may be some kind of "organ" that permeates, scans, and tastes shifting centers of experience, taking note of their fate and partnering their development - a kind of inner tuning sense in search of cultivation, spanning what we call conscious and unconscious life, mind and body, and testing the weather for favorable birth conditions. Often we do not know exactly what is happening or how, but sense something germinating. Domains open that are not confineable or restricted by the tools at hand - which is perhaps one reason why analysts are called toolmakers, as experience and the tools used to understand it become part of further birth processes. In this way, Eigen shows how the intimate fusion of psychological and spiritual currents generate new tastes of living